THE SEMANTICS OF FOCUS CONSTRUCTIONS IN AKOOSE - Apuge, Michael (PEOPLE: International Journal of Social Sciences, 2017)
This paper examines the semantics of focus constructions, with data drawn from Akoose. Each time a wh-phrase is used in the language, some material in the discourse is necessarily focused. Focusing in the language is complex, and two major types of focus phrases identified are those in which the wh-item moves to an XP containing a morphological focus marker on the one hand, and those in which an extracted wh-item moves to a matrix position where no focus morpheme is attested on the other. Given that the two constructions can be present in the same sentence, it becomes compelling to propose an empirical explanation of the phenomenon, with respect to the possible variance in the semantics of the structures. An issue of great concern that the paper attempts to bring to the fore, is that focus constructions have embedded semantic features that require sufficient empirical attention. Assuming the approaches adopted in Jackendoff (1972), Krifka (1992), Biloa (1992), E. Kiss (1998) and Aboh (2006), this paper re-orients discussions about the debate on focus constructions and meaning. It is argued that from a semantic point of view, Akoose differentiates two categories of Wh-fronting: topic focus and contrastive focus. The analysis also points to the finding that the feature specifications of these operations are different: while contrastive focus conveys independent presuppositions, topic focus does not. Even though the analysis has established a semantic dichotomy between the two operations, a theoretical insight of these phenomena predicts a uniform account. This is because the driving force for both types of constructions is to establish agreement relations between the probe and its goal, and thus satisfy feature valuation in minimalist terms. The paper concludes on the note that wh-expressions in Akoose denote different levels of focus operations, which have a distinct semantic bearing on the syntax of the language.